Pretransplant Interferon‐γ Secretion by CMV‐Specific CD8+ T Cells Informs the Risk of CMV Replication After Transplantation. Issue 3 (11th January 2013) - Cantisán, S.; Lara, R.; Montejo, M.; Redel, J.; Rodríguez‐Benot, A.; Gutiérrez‐Aroca, J.; González‐Padilla, M.; Bueno, L.; Rivero, A.; Solana, R.; Torre‐Cisneros, J.
<x xml:space="preserve">Abstract</x> In this prospective study we analyzed pretransplant interferon‐γ secretion by cytomegalovirus (CMV)‐specific CD8+ T cells to assess its possible utility in determining the risk of CMV replication after solid organ transplantation. A total of 113 lung and kidney transplant patients were enrolled in the study but only 55 were evaluable. All CMV‐seronegative recipients were pretransplant "nonreactive" (IFNγ <0.2 IU/mL) (11/11), whereas 30/44 (68.2%) CMV‐seropositive (R+) recipients were "reactive" (IFNγ ≥0.2 IU/mL) and 14/44 (31.8%) were "nonreactive". In the R(+) "nonreactive" group, 7/14 (50%) developed posttransplant CMV replication, whereas the virus replicated only in 4/30 (13.3%) of the R(+) "reactive" patients (p = 0.021). According to the best multivariate model, pretransplant "nonreactive" recipients receiving an organ from a CMV‐seropositive donor had a 10‐fold increased risk of CMV replication compared to pretransplant "reactive" recipients (adjusted OR 10.49, 95% CI 1.88–58.46). This model displayed good discrimination ability (AUC 0.80) and calibration (Hosmer–Lemeshow test, p = 0.92). Negative and positive predictive values were 83.7% and 75%, respectively. The accuracy of the model was 82%. Therefore, assessment of interferon‐γ secretion by cytomegalovirus (CMV)‐specific CD8+ T cells prior to transplantation is useful in informing the risk of posttransplant CMV replication in solid organ transplant patients.